Trauma Care Performance in Western China: A Single-Center Benchmark Analysis Using Provincial and National Trauma Registry Data - Li, Xixi; Liu, Yao; Zhao, Zhonglei; Zhou, Tong; Li, Yunxia; Yang, Bo (Celebes Nursing Journal, 2026)
Introduction: With urbanization, trauma has become a critical public health issue in western China. However, detailed performance evaluations of regional trauma centers using provincial and national registry benchmarks remain limited. Objective: This study aimed to investigate the clinical characteristics of trauma patients and evaluate the operational efficiency and outcomes of a tertiary trauma center in Suining using provincial and national benchmarks. Methods: A retrospective secondary analysis was conducted using the China Trauma Rescue Consortium (CTRC) database. Patient-level data were derived from a tertiary Grade A hospital in western Sichuan Province, while aggregated provincial and national CTRC data were used for benchmarking. A total of 8,257 patients treated between September 2021 and February 2025 were included. Descriptive statistics, univariate analysis, and multivariable binary logistic regression were performed using SPSS version 26.0. Statistical significance was set at p < 0.05. Results: Falls (including ground-level and height-related) and traffic-related injuries were the primary mechanisms of injury. The center demonstrated faster emergency department preparation time (4.03 min vs. 8.37 min nationally) and a lower mortality rate for severe trauma (1.67% vs. 2.32%). However, door-to-CT completion time (41.04 min) remained longer than benchmark values. The regression model showed high explanatory power (Nagelkerke R² = 0.96). Age (OR = 1.03, p = 0.01), ISS (OR = 1.24, p < 0.01), and GCS (OR = 0.62, p < 0.01) were significant independent predictors of 30-day mortality. Conclusion: This benchmarking analysis demonstrated strong early response performance but identified delays in diagnostic imaging workflows. Improving door-to-CT efficiency may further enhance trauma care outcomes in western China.